Evaluating the impact of COVID-19: A cohort comparison study of drug use and risky sexual behavior among sexual minority men in the U.S.A. (1st November 2020) - Starks, Tyrel J.; Jones, S. Scott; Sauermilch, Daniel; Benedict, Matthew; Adebayo, Trinae; Cain, Demetria; Simpson, Kit N.
Highlights: Marijuana and illegal drug use declined during the COVID-19 pandemic. Condomless anal sex with casual male partners declined during the COVID-19 pandemic. Associations between illegal drug use and sex outcomes were stronger during COVID. Abstract: Background: Sexual minority men who use drugs have high sexual HIV transmission risk. Sexual interactions may also increase COVID-19 risk.This study compared marijuana use, other illegal drugs use (i.e. cocaine/crack, methamphetamine, MDMA/ecstasy, GHB, and ketamine) and sexual behavior with casual partners among sexual minority cismen active on social networking and dating applications before and during the COVID-19 epidemic. Methods: This cohort-control study compared 455 adult respondents (surveyed May 6th to 17th, 2020) and a matched sample selected from 65, 707 respondents surveyed pre-COVID. Participants were recruited on social networking and dating applications and completed surveys online. Results: The proportion reporting marijuana use declined significantly in the COVID cohort (34.5 % versus 45.7 % pre-COVID, p < .001) as did their illegal drug use (11.0 % versus 22.9 % pre-COVID, p < .001). While the number of casual partners per month was stable, the proportion reporting condomless anal sex with casual partners declined significantly during COVID (26.4 % versus 71.6 % pre-COVID, p < .001). The effect of illegal drug use (excluding marijuana) on number of casual partners per month ( aRR = 1.45 pre-COVID versus 2.84, p < .01) and odds of condomless anal sex ( aOR = 2.00 pre-COVID versus 5.22, p = .04) were significantly greater in the COVID cohort. Conclusions: While the proportion of participants reporting drug use and condomless anal sex with casual partners declined in the COVID cohort, the association between drug use and sexual behavior was magnified. Sexual minority men who use drugs are significantly more likely to engage in sexual behaviors that place them at risk for HIV and COVID-19 transmission.